Titanium Meets Carbon: Enhanced Reusable Filters for Oil–Water Separation and Environmental Remediation - Amir-Hadi Boroumand; Kayla Laguana; Eric Dudley; Pilar Cuadros-Arias; Adrian Rubio; Zachary Shin; Jack Webster; Mingheng Li (Separations)
To mitigate the environmental effects of oil spills, a novel hydrophilic–oleophobic mixed-coated filter was developed for efficient oil–water separation and surface oil recovery. The coating consisted of titanium dioxide nanoparticles (TiO2) and ultra-fine carbon black powder, deposited onto a 304 stainless-steel mesh substrate via spray deposition, followed by high-temperature sintering. This process induced a phase transition in TiO2 from anatase to rutile, and formed a TiC khamrabaevite. The filter’s performance was evaluated using contact angle measurements and filtration tests with a motor oil–water mixture, while SEM, EDS, and XRD analyses characterized its morphology and coating structure. Contact angle testing confirmed that carbon modification significantly enhanced the oleophobicity of the TiO2 filter, and SEM imaging demonstrated higher substrate coating adhesion, enabling multiple reuse cycles. These findings highlight the potential of TiO2 carbon composite coatings in improving oil spill remediation technologies by offering a reusable and efficient filtration system.